Proceedings of the 2012 ACM Conference on Ubiquitous Computing 2012
DOI: 10.1145/2370216.2370363
|View full text |Cite
|
Sign up to set email alerts
|

Automatic analysis of eye-tracking data using object detection algorithms

Abstract: In this paper we investigate the integration of object detection algorithms with eye-tracking data. The emerging technology of lightweight mobile eye-trackers enables realistic in-the-wild user experience experiments. Unfortunately, mobile eye-trackers generate a large amount of video data, which up to now requires manual analysis. This time-consuming and repetitive task renders processing large datasets economically infeasible. Our main contribution is the use of object detection algorithms to perform this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Its anticipatory nature allows estimating which object will be used next [30,29]. Gaze has been successfully used to assist action and activity recognition [12,35,44,38] and supervised object recognition [53,11].…”
Section: Unsupervised Discovery Of Task-relevant Objects From Egocentmentioning
confidence: 99%
See 1 more Smart Citation
“…Its anticipatory nature allows estimating which object will be used next [30,29]. Gaze has been successfully used to assist action and activity recognition [12,35,44,38] and supervised object recognition [53,11].…”
Section: Unsupervised Discovery Of Task-relevant Objects From Egocentmentioning
confidence: 99%
“…Two consecutive image parts, Ω(I t ) and Ω(I t−1 ) belong to the same object if ||f t − f t−1 || < 1 , where 1 is the threshold selected to accept clustering consecutive image parts and ||.|| is the Euclidean distance (Algo. 1 L. [9][10][11][12][13][14]. The strict consecutive constraint between t and t−1 can be relaxed to allow proximity within a sliding window.…”
Section: Online Tro Discoverymentioning
confidence: 99%
“…offline processing. They presented first results of their prototype system a year later (De Beugher, Ichiche, Brône & Goedemé, 2012). While the described approaches do not focus on providing real-time performance on a mobile device, they are facing all of the computer vision (lighting, occlusions, and fast movements) and localization problems.…”
Section: Gaze Interaction In the Real Worldmentioning
confidence: 99%
“…The capability to estimate where a subject is looking is known as gaze estimation or eye-tracking. This technology has enhanced applications in a wide array of domains, including the measurement of advertising efficacy [1,2], instrumentation to enhance reading [3][4][5], automotive safety [6,7], pilot training [8][9][10], accessibility interfaces [11][12][13][14], and provide objective indicators of cognitive, psychiatric, and neurological states of individuals [15][16][17][18][19][20][21][22][23][24][25][26]. Even though research with specialized eye-tracking systems demonstrated that such systems can be used in many domains, the need to purchase expensive, specialized software and hardware to monitor the PoG limit the use of eye-tracking systems by consumers.…”
Section: Introductionmentioning
confidence: 99%